Methods of reducing the level of indoxyl sulfate – one of the most potent protein-bound uremic toxins. (1st October 2016) - Karbowska, Malgorzata; Kaminski, Tomasz; Pawlak, Dariusz
Abstract: Chronic kidney disease (CKD) is associated with accumulation of uremic toxins, especially indoxyl sulfate (IS). IS has multi-directional, adverse influence on the organism, and is connected with cardiovascular and bone diseases. These properties make reducing level of IS so important issue. This article reviews methods allowing to reduce concentration of IS. Authors present methods like dialysis, using albumin-binding competitors, trans-cellular transporters and adsorbents, facilitation of dissociation from albumin, as well as modification of diet and intestinal bacteria. Despite the continued improvement and invention of new strategies, development of effective and safety methods of IS removing is still a challenge for researchers.